Theory of planned behaviour for physical activity of adults living with physical disabilities: A replication systematic review - Myung Ha Sur; Deborah Shapiro (European Federation of Adapted Physical Activity, 2022)
Programme interventionists often determine best practices from systematic reviews of the literature. Interpretations of findings from systematic reviews, however, are susceptible to subjective decisions of the authors. Replication of systematic reviews by different authors on the same topic can increase the authenticity of findings, analysis, and interpretations. The purposes of the current paper were to (a) replicate a systematic literature review using the theory of planned behaviour (TPB) to understand the intention of adults living with physical disabilities to participate in PA, and (b) compare the findings with a published systematic literature review on the same topic. CINAHL, ERIC, SPORTDiscus, Medline, Psycinfo, and Pubmed databases were searched for eligible studies. A total of 11 articles were included for the current review. Intention was the strongest predictor for PA behaviour, with attitude and perceived behavioural control were also significant predictors for intention. Subjective norm had less influence but a distinct role shaping intention. A total of six of 11 studies overlapped with the comparison review. Selection of different studies were due to differences in search databases, search strategy, and inclusion and exclusion criteria. Inconsistency was also found in relationships among other components in the theory, with different interpretations made between the two reviews. The current replication review provides practical and research related implications that add to the understanding of the TBP for persons living with physical disabilities and the findings of the comparative review.